A Quantitative Study with SPSS 26: The Influence of Environmental Costs on Financial Performance with Managerial Ownership as Moderating - Drajat, Nabilah Aribah; Susilowati, Endah (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study investigates and evaluates how managerial ownership moderates the impact of environmental costs on financial performance. Methodology: 14 firms in the basic materials industry were listed on the Indonesia Stock Exchange for the 2021 - 2023 period as a consequence of the sample technique's usage of purposive sampling. The association between variables was examined using moderated regression analysis, which was performed using SPSS 26. Results: According to the study, financial performance is impacted by both environmental costs and managerial ownership, but the impact of environmental costs on financial performance is not mitigated by managerial ownership. Findings: Although managerial ownership can enhance financial performance, and this study emphasizes the significance of environmental costs, the relationship between environmental costs and financial performance is not moderated by the level of management's shareholdings. Novelty: It resides in combining corporate governance elements which are comparatively understudied with environmental concerns. Originality: The study's integration of management ownership and environmental cost viewpoints into a single model adds to Indonesia's corporate governance and sustainability literature. Conclusion: The study's results show that environmental costs reflect the company's responsibility for environmental issues important to stakeholders. The insignificance of managerial ownership moderation suggests that environmental decisions are not entirely determined by shareholders but rather by external stakeholder pressure and regulation.